Application of Natural Products in Neurodegenerative Diseases by Intranasal Administration: A Review - Yu Jin; Xinyu Ma; Shuo Liu; Shiyu Zong; Yunlong Cheng; Hong Zhang; Chunliu Wang; Ye Li (Pharmaceutics)
Natural products derived from traditional Chinese medicine have received significant attention as potential treatments for neurodegenerative disorders due to their wide availability, demonstrated efficacy, and favorable safety profiles. Intranasal delivery provides distinct advantages for targeting the central nervous system (CNS), enabling direct therapeutic agent delivery to the brain by bypassing the blood-brain barrier (BBB). This review evaluates natural products administered intranasally for neurodegenerative diseases (NDs), highlighting their therapeutic potential and addressing formulation challenges related to physicochemical properties. Strategic optimization approaches are proposed, including novel carrier systems, molecular modifications, and combination therapies. By discussing current difficulties and offering practical recommendations, this review aims to encourage further scholarly research and clinical application.